The Position of Signs of Hikayat in the Tafsir Al-Ibriz by Biṣri Musṫofa - Sartika, Ela; Jafrullah, Ruli; Dasuki, Kiki; Rimi, Abdul Rauf bin (Aqwal: Journal of Qur'an and Hadis Studies, 2025)
Background and Objectives: This study aims to examine the position of hikayat signs in Tafsir Al-Ibriz by Biṣri Musṫofa, a Nusantara mufassir known for his communicative and narrative approach in conveying the message of the Qur'an. The background of this research is based on the need to understand how hikayat, which are often considered mere folk tales or additional elements, actually play an important role in grounding the messages of the Qur'an to the general public. Method: This research uses a descriptive analysis method with a semiotic approach. Data collection techniques were carried out through a literature study of the Tafsir Al-Ibriz manuscript and the reference sources used, including classical tafsir such as Tafsir Al-Khazin. Main Results: The signs of hikayat in Tafsir Al-Ibriz do not merely serve as complementary stories, but as semiotic devices that connect the denotative aspects of the Qur'anic text with the connotative aspects of Javanese culture through the mechanism of myth as a second level of meaning, while also reconstructing classical sources such as Tafsir Al-Khazin in the local context of the archipelago. Contributions: This study contributes to enriching the study of Nusantara interpretation by revealing the strategic role of hikayat as a semiotic sign that reinforces the delivery of moral messages and contextualization of the Qur'an in Tafsir Al-Ibriz by KH. Biṣri Musṫafa. Conclusions: This study concludes that the use of hikayat signs in Tafsir Al-Ibriz is an effective semiotic strategy for grounding the message of the Qur'an through the integration of revelatory texts, classical exegetical traditions, and Javanese cultural symbols, thereby enriching the contextual and culturally sensitive hermeneutic tradition of the archipelago.